Light Metals Technology 2009 : selected peer reviewed papers from the 4th International Conference, organized by the CAST CRC, on behalf of the Global Light Metals Alliance, held from 29 June-1st July 2009 on the Gold Coast, Queensland, Australia - Keay, S. M.; Dargusch, M. S. (Trans Tech Publications, 2009)
The aim of this special collection was to provide an opportunity for companies, academic institutions and government research agencies to share, in a collaborative manner, their new research and development work. . The main focus was light metals and their applications. It is to be noted that there was a significant number of papers related to titanium research: due to the extended range of applications of titanium components and the growth in end-user demands for affordable manufacturing. As a result, the collection is truly representative of the three light metals: aluminium, magnesium and t.
Keywords: Solidification -- Congresses.; Die-casting -- Congresses.; Light metals -- Congresses.; Founding -- Congresses.; elektronické knihy; electronic books